A Systematic Literature Review on Flipped Classrooms in Elementary Schools for Advancing 21st-Century Learning - Susanti, Susanti; Maftuh, Bunyamin; Dwiputra, Dimas Febriansyah Krisna (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2024)
Implementing the flipped classroom in elementary schools has become a crucial learning alternative in responding to the demands of 21st-century learning, which prioritizes active student engagement and maximizing technological utilization. This research aims to conduct an in-depth analysis of existing empirical research regarding implementing the flipped classroom in elementary schools to obtain comprehensive information regarding developments, potential, and challenges in its implementation. The systematic literature review followed PRISMA 2020 guidelines and utilized data from Scopus and ERIC databases. Out of f 133 articles, 29 met inclusion criteria and were analyzed using the meta-synthetic approach. The findings revealed limited progression of flipped classroom implementation in Indonesian elementary schools, with global development fluctuations. Implementation advantages included increased student engagement, comprehension, and motivation, aligning with 21st-century learning needs. Technology, particularly instructional videos, played a pivotal role, while challenges included material readiness, technology access, and parental support. These findings offer an overview of the current circumstances surrounding the implementation of flipped classrooms and highlight the potential and obstacles that need to be considered to increase their effectiveness at the elementary school level. In conclusion, integrating flipped classrooms emerges as a pertinent alternative to address the demands of 21st-century learning. Nevertheless, it is imperative to recognize that the identified challenges, coupled with the restricted implementation in Indonesia, warrant further research.